Are bioplastics safe? Hazardous effects of polylactic acid (PLA) nanoplastics in Drosophila - Alaraby, M.; Abass, D.; Hernández, A.; Marcos, R. (Spanish Journal of Environmental Mutagenesis and Genomics, 2024)
Background: While the production of bioplastics increases continuously, there is a gap of information on the hazardous impact of their degradation products (micro/nanoplastics, MNPLs). Aim: To understand the potential health risks associated with the exposure to MNPLs of bioplastics. Methods: To address this issue, Drosophila melanogaster as a versatile terrestrial in vivo model was employed, and polylactic acid nanoplastics (PLA-NPLs), as a proxy for bioplastics, were tested as a material model. A wide battery of approaches has been applied in this study including internalization, gene expression, oxidative stress, and genotoxicity. Results: The harmful effects were determined in larvae exposed for 4 days to different concentrations (25, 100, and 400 μg/mL) of 463.9 ± 129.4 nm PLA-NPLs. Transmission electron microscopy (TEM) and scanning electron microscope (SEM) approaches permitted the detection of PLA-NPLs in the midgut lumen of Drosophila larvae, interacting with symbiotic bacteria. Enzymatic vacuoles were observed as potential carriers, collecting PLA- NPLs and enabling the crossing of the peritrophic membrane, finally internalizing into enterocytes. Although no toxic effects were observed in the egg-to-adult survival, the cell uptake of PLA-NPLs causes cytological disturbances and the formation of large vacuoles. The translocation across the intestinal barrier was demonstrated by their presence in the hemolymph. Furthermore, PLA-NPL exposure triggered intestinal damage, oxidative stress, DNA damage, and inflammation responses, as evaluated via a wide set of marker genes. Collectively, these structural and molecular interferences caused by PLA-NPLs generated high levels of oxidative stress and DNA damage in the hemocytes of Drosophila larvae. Conclusions: The observed effects point out the need for further studies aiming to deepen the health risks posed by bioplastics before considering their uses as a safe plastic alternative to the petroleum-based plastics.